Micro and Macroeconomic Determinants of Indonesian Government"™s Bonds Liquidities in the Secondary Market (2012-2016) - Soebagio, Yogie Kristianto; Solikin, Akhmad (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
Despite having registered the trade volume since 2005, Indonesia's bond market trading and liquidity level in the secondary market are still the lowest in Asia. Neighboring countries like the Philippines and Singapore started registering trading volume records in the same year as Indonesia has exceeded the liquidity level of the Indonesian market. This raises the question of what makes the rate of development in Indonesia's bond market not as fast as other countries in Asia. Therefore, this article aims to analyze the determinants of liquidity in the secondary market of Indonesian bonds, especially government bonds. In the case of Indonesia, research on government liquidity is still limited. Various studies have been conducted to determine the factors affecting liquidity and also the method to calculate them but mostly focus on private bonds. This research uses the level of liquidity of bonds based on turnover ratio as a dependent variable and variable of maturity rate, coupon rate, exchange rate, stock price index, and lending rate as independent variables. The method used is multiple linear regression. The results show that the liquidity of 10-years benchmark government bonds in Indonesia is significantly influenced by the coupon rate and lending rate positively but influenced by the exchange rate and stock price index negatively. These results indicate that liquidity is influenced by macroeconomic variables. Thus, the Indonesian government should monitor macroeconomic indicators closely and change policy related to its bonds accordingly.